Perencanaan kebutuhan bahan baku untuk kelancaran produksi guna memenuhi permintaan (Studi kasus : UD. Maju Jaya) - Cahyo, Chandra Dwi; Mundari, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Maju Jaya is a furniture manufacturer in Surabaya that faces challenges in managing raw materials, especially camphor wood lonjoran, which causes production delays and customer dissatisfaction. This study aims to improve efficiency through forecasting raw material requirements using the Exponential Smoothing method with alpha 0.2, which has been proven to produce the lowest MAD value. The forecast results are used in production planning using the Chase Strategy method to flexibly adjust workforce capacity. Material Requirements Planning (MRP) analysis shows the need for repurchasing certain raw materials to prevent shortages. Stock monitoring and timely procurement of raw materials are recommended to ensure smooth operations and meet delivery schedules.